Long Non-coding RNA TMEM220-AS1 Suppressed Hepatocellular Carcinoma by Regulating the miR-484/MAGI1 Axis as a Competing Endogenous RNA - Cao, Cong; Li, Jun; Li, Guangzhi; Hu, Gaoyu; Deng, Zhihua; Huang, Bing; Yang, Jing; Li, Jiequn; Cao, Song (Frontiers in Cell and Developmental Biology, 2021)
Long non-coding RNAs (lncRNAs) have a considerable regulatory influence on multiple biological processes. Nevertheless, the role of TMEM220-AS1 in hepatocellular carcinoma (HCC) remains unclear. We used The Cancer Genome Atlas (TCGA) database to analyze the differentially expressed lncRNAs. qRT-PCR was used to verify the results for a large population. The in vitro effects of TMEM220-AS1 on HCC cells were determined using Cell Counting Kit-8 (CCK-8), 5-ethynyl-2′-deoxyuridine (EdU), flow cytometry, and Transwell assays in HCC cells. We used qRT-PCR and western blotting to identify the epithelial-mesenchymal transition (EMT). Moreover, we performed bioinformatics analysis, western blotting, dual luciferase reporter gene assay, RNA pull-down, and RNA binding protein immunoprecipitation (RIP) to investigate the underlying molecular mechanisms of TMEM220-AS1 function. Finally, the function of TMEM220-AS1 was verified in vivo. The results showed that TMEM220-AS1 was expressed at considerably low levels in HCC. It was demonstrated that malignant phenotypes and EMT of HCC cells were promoted by the knock down of TMEM220-AS1 both in vivo and in vitro. TMEM220-AS1, which was detected primarily in the cytoplasm, functioned as an miRNA sponge to bind miR-484 and promote the level of membrane-associated guanylate kinase, WW, and PDZ domain containing 1 (MAGI1), thereby curbing the malignant phenotypes of HCC cells. In conclusion, low levels of TMEM220-AS1 promote proliferation and metastasis through the miR-484/MAGI1 axis in HCC.